Effect of potassium chloride amount on structures of hydrothermally grown KNbO3 nanostructure. (May 2014) - Cao, H.; You, C.; Yu, J.; Cao, B.; Yu, B.; Xin, H.; Li, Y.
<x content-type="archive" xml:space="preserve">Abstract</x> KNbO3 nanocrystals were synthesised by hydrothermal process with KOH, Nb2O5, KCl and H2O mixture as principal raw materials. Pure phase orthorhombic and rhombohedral structure crystals were formed. The nanocrystals were good crystalline, and the morphology has been greatly changed when different amounts of KCl were added. The diameter of rods was ∼500 nm, which were formed when the molar ratios of KOH and KCl are 1∶0·030 and 1∶0·060; the nanorod yield was improved greatly. Two different structure crystals showed different peak positions at ∼250 cm−1 for rhombohedral KNbO3 and 279 cm−1 for orthorhombic KNbO3 in Raman spectrum.